Dampak Penggunaan Media Sosial terhadap Sikap Toleransi Mahasiswa PPKN Semester 2 Universitas Cenderawasih - Paotonan, Nesliani (Faculty of Teacher Training and Education of Undaris, 2025)
The rapid development of social media as a product of the digital revolution has significantlyinfluenced various aspects of life, including students' attitudes toward tolerance. This study aims to analyzethe impact of social media usage on the tolerance attitudes of second-semester Civic Education (PPKN)students at Cenderawasih University, using a correlational quantitative approach. Data were collectedthrough closed questionnaires distributed to 41 respondents and analyzed using Pearson’s correlation andsimple linear regression tests with SPSS 25.0.The results revealed a significant positive relationship between the intensity of social media use andtolerance attitudes (r = 0.711, p < 0.001), with social media contributing 50.5% to tolerance formation. Thedominant platforms used were TikTok (46.3%) and Instagram (34.1%), which served as effective mediumsfor multicultural learning through creative content. However, 65% of respondents reported exposure todiscriminatory content, while only 40% actively sought content related to cultural diversity. These findingssuggest that social media has a dual role—enhancing tolerance through positive interactions whilepotentially diminishing it through exposure to harmful content.This study recommends integrating digital literacy into the Civic Education curriculum andoptimizing social media platforms to promote inclusive values. The implications highlight the need for data-driven strategies to maximize social media’s positive impact while mitigating its risks in fostering toleranceamong students in multicultural environments such as Papua.Keywords: Social media, tolerance, Civic Education students, Cenderawasih University.